Effects of Neuro-Linguistic programming imagery on Kickboxers' performance (Funded Work) - MEISAM SAVARDELAVAR,; GARRY KUAN,; SOMAYEH RASHIDFARD, (International Journal of Pharma and Bio Sciences, 2018)
Mental imagery is a cognitive practice that has been widely employed for facilitating skills learning and enhancing sporting performance. Neuro-Linguistic Programming is a cognitive behavioural model used successfully for changing thoughts, feelings, and human behaviour. Although this model has been widely used in education and medicine, it has not been employed systematically using imagery related techniques for enhancing sports performance in the applied field. Thus, this study aimed to examine the efficacy of Neuro-Linguistic Programming-based imagery intervention on the performance of youth and adult kickboxers. This study employed a pre-test, intervention, post-test study design on 24 youth amateur kickboxers age ranging from 18 to 23 (M = 19.5), and 24 adult amateur kickboxers age ranging from 24 to 31 (M= 26.5), who volunteered to participate in this study. The pre-test was conducted by assessing the number of successful counter-attacks. Then, participants undertook the intervention by rehearsing the mental imagery twice a week together with specific kickboxing training techniques three times a week for seven weeks. Finally, the post-test was conducted upon completion of the intervention similar to pre-test. The results showed that the number of successful counter-attacks in both youth and adult groups increased significantly after using imagery intervention, t(23) = - 6.08, p =.001, and t(23) = - 2.345, p =.030, respectively. The results of this study suggest that Neuro-Linguistic Programming-based imagery intervention could be a useful intervention tool for enhancing kickboxing performance.